Analisa Ketahanan Tubuh Benih Hibrida Nila Larasati (Oreochromis niloticus) Generasi 5 (F5) Yang Di Infeksi Bakteri Streptococcus agalactiae Dengan Konsentrasi Berbeda - Santoso, Beny Budi; Basuki, Fajar; Hastuti, Sri (Journal of Aquaculture Management and Technology, 2013)
Seed quality can be increased by fish genetic amelioration. Good quality seed is characterized by its immunity from diseases. Nila Larasaty (O. niloticus) Hybrid F5 is ameliorated genetic product of cross breeding between Nila Gift F5 female and Nila Singapore F5 male. This research aims to know Nila Larasati F5 Hybrid’s immunity system infected by S. agalactiae. Completely randomized design (RAL) is applicated on the research with 3 treatments and 3 repetitions, which treatments are: A (105 CFU/ml bacteria); B (107 CFU/ml bacteria) and C (109 CFU/ml bacteria). This research done in 35 days started from September until October 2012 at 2nd Class of BKIPM, Semarang Examined variabels are erythrocyte, leucocyte, hemoglobin, trombocyte, hematocrite, blood glucose, and survival rate. The result shows that erythrocyte highest on treatment C (1,87±0,19x106 sel/mm3); leucocyte highest on B (126,53±13,36 x103sel/mm3); hemoglobin on C (8,43±0,40 g/dl); trombocyte on B (50,33±45,72x103sel/mm3); hematocrite on C (9,20±1,71%); blood glucose on A (57,07±23,10 mg/dl); and survival rate highest on A (97,22±4,81%). Water quality parameters checked i.e DO (Dissolved Oxigen) 0,8 – 1,4 mg/l; pH 7,7 – 7,9; tempeature 28 – 28,3°C and ammonia 0,173 – 0,215 mg/l. Also the result shows that infection by S. agalactiae with different concentration has no significant effect (P>0,05) on seed of Nila Larasati F5 hybrid’s immunity system.